Reassessing car scrappage schemes in selected OECD countries: A synthetic control method application - Hendrik Lüth (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2021)
In this study the impact of car scrappage schemes is reassessed and disentangled for six OECD countries, namely Japan, Germany, South Korea, the Slovak Republic, the United Kingdom and the United States, following a rather novel empirical approach, the Synthetic Control Method using Time Series (SCMT). Scrappage schemes were implemented in many countries in response to the Great Recession of 2007-2009 and were hotly debated among economists and policymakers, as many disagreed about the sustainability of the programs' effects. With the use of the synthesized control units constructed transparently with SCMT, the effects of car scrappage schemes on vehicle registrations can be observed and calculated over time. Results suggest that despite scrapping subsidies induced some intertemporal substitution, net effects on car registrations remained positive in all investigated countries with the notable exception of the United Kingdom, where additional sales were completely crowded out by subsequent consumer reticence.
Keywords: L52; L62; 330; synthetic control method; scrappage schemes; automotive industry; intertemporal substitution; SCMT; pull-forward effects